High-tech IDs : from finger scans to voice patterns - Tocci, Salvatore (New York : F. Watts, 2000)
Describes a variety of devices and systems used for identifying individuals, including finger and hand scans, iris and retinal scans, fingerprinting, DNA fingerprinting, and voice pattern recognition, and gives examples of how they are used.
Includes bibliographical references (p. 121) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Biometry -- Juvenile literature; Identification -- Juvenile literature; Biometry; Biometry; Identification